Selective filtration of oil/water mixtures with bioinspired porous membranes. Issue 52 (27th June 2017) - Zeiger, Claudia; Kumberg, Jana; Vüllers, Felix; Worgull, Matthias; Hölscher, Hendrik; Kavalenka, Maryna N.
Abstract : Membranes inspired by special wetting properties of aquatic plant leaves enable selective removal of either oil or water from oil/water mixtures by filtration. Abstract : Membranes inspired by special wetting properties of aquatic plant leaves enable selective removal of either oil or water from oil/water mixtures by filtration. Here, we introduce polymeric micro- and nanohair-covered porous membranes fabricated using highly scalable fabrication methods: hot pulling and perforation with microneedles. The as-prepared superhydrophobic/superoleophilic oil-removing membranes are converted into underwater superoleophobic water-removing membranes by argon plasma treatment. Membrane permeability and breakthrough pressures are analyzed and compared to theory, and the efficiency of both types of membranes for oil/water separation is demonstrated.